Preoperative respiratory training with incentive spirometry for the prevention of pulmonary complications after liver surgery- a randomized pilot trial (PreSpi Trial) - Giehl-Brown, Esther; Rangnick, Henriette M.; Schweipert, Johannes Tobias; Halank, Michael; Koschel, Dirk; Weitz, Jürgen; Riediger, Carina (Langenbeck's archives of surgery, 2025)
Postoperative pulmonary complications (PPCs) following liver surgery are associated with considerable morbidity and mortality. Nevertheless, data regarding the effectiveness of short-term, self-conducted preoperative respiratory training on pulmonary function and its influence on postoperative recovery are limited.